Substorm Induced Nighttime Plasma Flow Pulsations Observed by ROCSAT‐1 at Topside Ionosphere. Issue 3 (7th March 2023) - Su, S.‐Y.; Sun, Y.‐Y.; Chao, C.‐K.; Tsai, L.‐C.; Liu, C. H.
Abstract: The Republic of China Satellite‐1 orbiting at 600 km topside ionosphere has observed the topside ionospheric plasma flow pulsations induced by the substorm onsets. These pulsation events indicated that the plasma flow pulsations mainly oscillate in the two mutually perpendicular directions with respect to the geomagnetic field lines. The field‐aligned flow as well as the ion density indicates almost no variation. This implies that the pulsation events are of Alfven wave in nature. The Hilbert‐Huang transform analysis is applied to study the dominant wave frequencies and the polarization in the two perpendicular components of plasma flows (i.e., the perturbed electric/magnetic fields). The hodograms of the polarization in the Pi1 frequency is shown to be linearly polarized, while the left‐handed polarization is seen in the Pi2 frequencies that are in harmonic relationship. These plasma flow pulsations in the nighttime topside ionosphere are caused by the field‐line‐resonance magnetic field pulsations converted from the inward propagated compressional disturbance across the nighttime magnetosphere/plasmasphere which is originated at the near‐Earth magnetotail at the substorm onset. Plain Language Summary: The Republic of China Satellite‐1 (ROCSAT‐1) spacecraft orbiting at 600‐km altitude observed three cases of plasma flow oscillations near the midnight sector. The plasma flow oscillation is observed in the two flow components that are perpendicular to the Earth magnetic field lines. When looked down along the magnetic field lines, the oscillation pattern is rotating in the anti‐clockwise direction describing a circle or an ellipse. Such oscillation pattern fits the so‐called Alfven wave description. The cause of such oscillation comes from a disturbance that is originated in the back side of the Earth magnetosphere during a magnetosphere substorm period. The substorm induced disturbance then propagates across the magnetic field lines toward the Earth. The propagated disturbance is in a form of compressional magnetosonic wave like a disturbance propagating inside a water‐filled balloon being hit by a hand on the balloon. The compressional magnetosonic wave is then converted to a transverse Alfven wave that propagates along the magnetic field line as observed by ROCSAT‐1. Key Points: Nighttime topside ionospheric plasma flow pulsations are induced by the substorm onset Pulsation polarizations are either linearly or left‐hand circularly/elliptically polarized Pulsations have Alfven wave characteristics